SEJARAH SENAM DAN JENIS-JENIS SENAM DI SD/MI - Aulia Fitri Damayanti; Ahmad Tarmizi Hasibuan (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2021)
This research method is the Library Research method with a qualitative research type.Improving the quality of physical fitness in SD/MI through gymnastics can make the bodyhealthy. Doing gymnastics can make children aware of the importance of maintainingphysical health both through sports and physical movement. Each exercise also has adifferent movement. Gymnastics also has benefits for the human body including: smoothingthe circulation of the human body, helping the respiratory system, strengthening themuscles of the hands and feet. The purpose of this study was to determine the history ofgymnastics and the types of gymnastics in SD/MI. The history of the development ofgymnastics in the world began in ancient times BC, both in the western world and in theeastern and middle eastern worlds. Gymnastics itself entered in Indonesia and becameknown in 1912 during the Dutch colonial era. The inclusion of gymnastics makes physicaleducation a compulsory subject in schools. By itself, gymnastics as part of physicaleducation is also taught in schools. Gymnastics is divided into 6 groups according to FIG.First, Aristic Gymnastics (artistic gymnastics). Second, Sportive Rhythmic Gymnastics(sportive rhythmic gymnastics). Third, acrobatic gymnastics. Fourth, Sport AerobicsGymnastics (sports aerobics). Fifth, Trampoline Gymnastics (trampolinning). Sixth,General Gymnastics (general gymnastics). Meanwhile, at the Elementary Age or SD/MIlevel, there are three types of gymnastics. First, Basic Gymnastics. Second, RhythmicGymnastics. Third, Floor Gymnastics or Agility